Comparative Study of Outcome of Brain Abscess Treated by Aspiration Versus Excision With Capsule (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: There are two common surgical options i.e. Burr hole aspiration and Excision with capsule with craniotomy in the treatment of brain abscess. The purpose of the study is to compare the two surgical methods (Burr hole and craniotomy) used as treatment for cerebral abscess and its outcome in terms of radiological clearance on brain CT, improvement of neurological status, the need for repeated surgery, and mortality and morbidity at six months after surgery. Materials and methods: The study was conducted in the Neurosurgery ward of Chittagong Medical College Hospital in a period (July 2012 to June 2014) of 24 months period. A total of 34 patients were taken as study subjects where two groups were made. Group A (n=20) patients were treated by bur rhole aspiration under general anesthesia and Group B (n=14) patients were treated by craniotomy and excision with capsule under general anesthesia. Peroperative and postoperative outcome was evaluated and compared. The clinical success of the both procedures, length of hospital stay, surgery related complications and neurological outcome were analyzed. Results: Among the 34 patients in both groups postoperative clinical data showed in group B there are more incidence of headache, vomiting, neurological deficit and seizure in three postoperative days than Group A patients. Few cases of fever was found in both groups. Two cases of wound infection was found in Group B at 7 postoperative days. Post operative GCS where Glasgow Coma Scale (GCS) was found to be gradually improving in Group A patients whereas in Group B 2 cases had GCS within 8-12 after 7 postoperative days. Regarding outcome during discharge improved GCS(>12) were found all in group A patients but it was less in Group B patients. Vomiting also found nil in Group A patients whereas in group B it was present in 2 cases during discharge. Seizure and neurological deficit was found nil in Group A patients but 4 cases in Group B had seizure and neurological deficit. There was one case in Group B who had wound infection. Evaluation of post operative hospital stay among the 34 patients in both groups were statistically significant less time was needed in Group A patients than Group B (p